Antecedent Organizational Citizenship Behavior and Service Quality - Jufrizen Jufrizen; Muslih Muslih; Dedek Kurniawan Gultom (Jurnal Bisnis dan Manajemen, 2022)
This study aims to examine the antecedents of Organizational Citizenship Behavior and Service Quality. This study used an explanatory research approach, which aims to explain the causal relationship between the research variables and the test hypothesis. The population in this study were all employees from the 5 best private Islamic universities in North Sumatra and the sample size in this study was 200 employees. The data analysis method used in this research is factor analysis and the Structural Equation Model. The results of the study showed that work ethics, organizational commitment and motivation have a significant positive effect on Organizational Citizenship Behavior. Organizational Citizenship Behavior has a significant positive effect on Service Quality at Private Universities in North Sumatra.